Apical aneurysm and left ventricular hypertrophy - Helena Nogueira Soufen; Clovis de Carvalho Frimm; Luiz Alberto Benvenuti; Charles Mady (Arquivos Brasileiros de Cardiologia, 2000)
A 59-year-old woman presented with an embolic transient ischemic attack and a history of controlled hypertension for 16 years. Both echocardiogram and MRI showed severe biventricular hypertrophy and an apical aneurysm with a thrombus. The occurrence of an apical aneurysm in the presence of cardiac hypertrophy is a rare finding and has been described in patients with hypertrophic cardiomyopathy. However, it has not been reported in patients with systemic arterial hypertension. In this patient the lack of a relationship between the severity of the hypertrophy and the levels of blood pressure, together with the presence of histologic disorganization of myocardial cardiac muscle cells by endomyocardial biopsy suggested the diagnosis of hypertrophic cardiomyopathy.